Advanced engine performance diagnosis - Halderman, James D. 1943- (Prentice Hall multimedia series in automotive technology, 2006)
Based on the premise that simple problems should always be checked first, this practical, hands-on book introduces the diagnosis and troubleshooting of automotive engine control systems. With a very technical but easy-to-read and understand presentation this book serves as a single source for information on advanced engine performance diagnosis. Topics include digital storage oscilloscopes, fuel injection and ignition system diagnoses, five-gas exhaust analysis, emission testing, and more. This edition has been updated to include even more detailed scope (DSO) and current ramping tests plus extensive scan tool diagnosis. For those who need to pass the ASE Engine Performance certification test as well as the Advanced Level Engine Performance (L1) test.